2016
DOI: 10.18632/oncotarget.12051
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of successful on-purpose tumor biopsies in metastatic cancer patients included in the SHIVA prospective clinical trial

Abstract: PURPOSETo identify patient/tumor characteristics associated with success of biopsy in patients who received multiple lines of chemotherapy.METHODSPatients with refractory cancer from our center, who were included in a prospective randomized phase II trial comparing targeted therapies based on molecular profile of tumors versus conventional chemotherapy, were retrospectively included in this IRB-approved study. All patients had a biopsy of a tumor lesion performed during surgery, or using CT/palpation/endoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(39 reference statements)
0
5
2
Order By: Relevance
“…In contrast, lesions not exposed to prior systemic therapy or systemic therapy closer to time of biopsy might be less likely to have developed as much fibrosis. This finding contrasts with prior work showing that ongoing chemotherapy at the time of biopsy reduces yield [ 30 ] or has no effect on biopsy yield [ 28 ]. The difference might be attributable to the different tumor types included in those studies compared to ours.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…In contrast, lesions not exposed to prior systemic therapy or systemic therapy closer to time of biopsy might be less likely to have developed as much fibrosis. This finding contrasts with prior work showing that ongoing chemotherapy at the time of biopsy reduces yield [ 30 ] or has no effect on biopsy yield [ 28 ]. The difference might be attributable to the different tumor types included in those studies compared to ours.…”
Section: Discussioncontrasting
confidence: 98%
“…Unlike prior studies that showed no associated between lesion size and adequacy of biopsy [ 21 , 28 , 30 ], in our study lesions <3 cm in maximal diameter had higher odds (OR 2.72) of adequacy for NGS than larger lesions on multivariate analysis. This result was unexpected because of the ease with which larger lesions are biopsied.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Eligible patients are randomized to molecularly targeted therapies or to treatment at the physician's choice. Treatment cross over is possible at the time of disease progression [12,13].…”
Section: The Concept Of An Oncology Center Network With Access To Molmentioning
confidence: 99%